Modified Intra Prediction Unit Size Selection Algorithm for H.265/HEVC Compression Systems; Applied Mathematical Sciences; Vol. 9, № 140 - Ponomarev O. G. Oleg Gennadjevich; Sharabayko M. P. Maksim Pavlovich; Tyo D. Yu. Dmitry Yurjevich; Strelnikov S. E. Sergey Evgenjevich (2015, 2015)
Title screen